EDUCATION FOR THE IMPLEMENTATION OF 6 M AND THE COVID-19 BOOSTER VACCINATION - Lono Wijayanti; Riska Rohmawati; Rahayu Anggraini; Siti Damawiyah; Erika Martining Wardani (Community Service Journal of Indonesia, 2023)
Positive cases of covid-19 will still exist if the community is negligent in implementing health protocols and inappropriate information related to continued or booster doses of Covid-19 vaccination in the community can cause doubt and anxiety, and if this is not immediately addressed then the community refuses to do so. booster vaccination because they feel that only one vaccination is enough. The purpose of this community service activity is to increase knowledge and health behavior in implementing the 6M (Mencuci Tangan, Memakai Masker, Menjaga Jarak, Menjauhi Kerumunan, Menjaga Pola Makan Sehat, Istirahat Cukup, dan Mengurangi Mobilitas) and willing to take further doses of Covid-19 vaccination. The method used in this activity is to provide health education to cadres and the public about the importance of implementing 6M and the Covid-19 booster vaccination. This community service activity was carried out for one week, attended by 65 health cadres and the community. The results of this community service activity show an increase in knowledge about the application of health protocols and the importance of the Covid-19 booster vaccination and the community is very enthusiastic about participating in this activity.